2021
DOI: 10.1038/s41435-021-00156-2
|View full text |Cite
|
Sign up to set email alerts
|

Population-specific diversity of the immunoglobulin constant heavy G chain (IGHG) genes

Abstract: Human immunoglobulin G (IgG) molecules, IgG1, IgG2 and IgG3, exhibit substantial inter-individual variation in their constant heavy chain regions, as discovered by serological methods. This polymorphism is encoded by the IGHG1, IGHG2, and IGHG3 genes and may influence antibody function. We sequenced the coding fragments of these genes in 95 European Americans, 94 African Americans, and 94 Black South Africans. Striking differences were observed between the population groups, including extremely low amino acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…For example, the G1m-1,3 haplotype is dominant in individuals of European descent, while the G1m1,17 haplotype is more prevalent, reaching frequencies over 80%, within African and Asian populations as well as American and Australian First Nations peoples. 3,15,16 Here, we demonstrate that certain commercial anti-IgG1 antibodies display variable binding to G1m-1,3 and G1m1,17 IgG1 variants. We show that a detection antibody targeting the IgG1 hinge region preferentially binds G1m1,17 over G1m-1,3 variants, while IgG1 and pan-IgG clones raised against the Fc portion bind G1m-1,3 and G1m1,17 IgG1 equivalently.…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…For example, the G1m-1,3 haplotype is dominant in individuals of European descent, while the G1m1,17 haplotype is more prevalent, reaching frequencies over 80%, within African and Asian populations as well as American and Australian First Nations peoples. 3,15,16 Here, we demonstrate that certain commercial anti-IgG1 antibodies display variable binding to G1m-1,3 and G1m1,17 IgG1 variants. We show that a detection antibody targeting the IgG1 hinge region preferentially binds G1m1,17 over G1m-1,3 variants, while IgG1 and pan-IgG clones raised against the Fc portion bind G1m-1,3 and G1m1,17 IgG1 equivalently.…”
Section: Introductionmentioning
confidence: 58%
“…As immunoglobulin allotypes are inherited in a Mendelian fashion, IgG1 haplotypes tend to cluster ethnically and geographically. For example, the G1m‐1,3 haplotype is dominant in individuals of European descent, while the G1m1,17 haplotype is more prevalent, reaching frequencies over 80%, within African and Asian populations as well as American and Australian First Nations peoples 3,15,16 …”
Section: Introductionmentioning
confidence: 99%
“…The constant region of the IgGs is encoded by the IGHG1-4 genes, which are highly homologous and polymorphic. IGHG polymorphisms have been associated with differences in the IgG half-life and effector functions [3]. Subsequently, they might be associated with heterogeneous neutralization-capacity and increased risk for infection and viral disease outcome.…”
Section: Introductionmentioning
confidence: 99%
“…IgG3 (encoded by the IGHG3 gene) is the unique subclass that varies in its hinge length by different copies of a 15 amino acid exonrepeat. The most common IGHG3 has 4 repeats, and a less common 3-repeats and rare 5-repeats have been reported [3]. Some studies have demonstrated that increased hinge length drives better phagocytosis and neutralization capacities, what is likely a consequence of greater flexibility that facilitates the binding to multiple epitopes [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, no current AIRR-seq strategy resolves the complete heavy chain transcript, including all IGHC exons alongside the recombined IGHV, IGHD, and IGHJ genes. Our team has recently shown that population-based polymorphisms within the IGHV, IGHD, IGHJ and IGL loci are far more extensive than previously known; the IGHC region has also been shown to contain genomic diversity, although the extent of this diversity has likely not been fully explored (20)(21)(22)(23)(24)(25)(26)(27). Although it is understood that the Fc domain mediates Ab effector functions, there is limited knowledge as to how genetic variation in this region may impact functional capabilities or posttranslational modification (5,28,29).…”
Section: Introductionmentioning
confidence: 99%